EXPLORING NETWORKED IDENTITIES OF INDONESIAN HIJABERS - Alila Pramiyanti (Lingkar Studi Komunikasi (LISKI), 2019)
This paper examines the networked identities of the Indonesian hijabers (a term for hijab-wearing woman who is fashion conscious). This study was undertaking in-depth interviews and participant-observations towards twenty-six hijabers who are actively taken part as a committee in the hijab communities. The term networked identity has been developed to adjust how community represents identity in the internet era. Most of the communities consider the importance of dynamic interactions and communication in the construction of networked identities. They mostly use Instagram for external communication channel along with WhatsApp and Line for internal communication channel. These hijabers consciously believe on their identities should be representing the images of pious Muslimah (a term for Muslim woman). Additionally, they also represent and communicate their networked identities as active and modern Muslim women that generate new figures of Indonesian young Muslim women.